2017
DOI: 10.1039/c7ra06958h
|View full text |Cite
|
Sign up to set email alerts
|

Some new azobenzene liquid crystals involving chalcone and ester linkages

Abstract: New azobenzene derivatives containing chalcone and ester linkages showed photo-responsive behaviours and alkoxy chain and terminal group effects on their mesomorphic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…20 One method for achieving such multi-responsive materials is the introduction of photochromic materials into the liquid crystal. [21][22][23][24] The azobenzene functional group is known to have a facile E/Z isomerization upon irradiation with UV light (Figure 1a). However, because of the propensity of azobenzenes to π-stack, unless specifically designed otherwise, azobenzene LC materials typically exhibit thermotropic liquid crystalline behaviour at temperatures higher than practical for industrial applications, with many reported melting points well above 100 • C. [25][26][27][28] For this reason many investigations focus on doping other liquid crystalline systems with azobenzene chromophores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 One method for achieving such multi-responsive materials is the introduction of photochromic materials into the liquid crystal. [21][22][23][24] The azobenzene functional group is known to have a facile E/Z isomerization upon irradiation with UV light (Figure 1a). However, because of the propensity of azobenzenes to π-stack, unless specifically designed otherwise, azobenzene LC materials typically exhibit thermotropic liquid crystalline behaviour at temperatures higher than practical for industrial applications, with many reported melting points well above 100 • C. [25][26][27][28] For this reason many investigations focus on doping other liquid crystalline systems with azobenzene chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…However, the observed LC transition temperatures, from 95-105 • C, remain much greater than our room-temperature target. Other routes of investigation have included the incorporation of biologically relevant functional groups, such as chalcone and ester linkages 24 and bent molecule based liquid crystals, which have their own distinct self-assembled LC structures. 25,31 Zhu et al performed a study introducing chalcone and ester linkages into a series of azobenzene molecules, however, the relevant thermotropic LC temperature transitions were found to be in excess of 110 • C. Clearly this line of investigation could benefit from a better understanding of the driving forces for formation of lyotropic LC systems, which can occur at biologically relevant temperatures because of their similarity to biological structures such as cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The compound 3a-8 underwent crystallization before melting at the second heating. This phenomenon indicated that the compounds did not crystallize during cooling from isotropic liquids, but in the further heating process, the molecules were rearranged orderly with the increase of molecular fluidity, and new crystals were formed [ 35 ]. After further heating, the compounds melted into isotropic liquids.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1a–1c and acyl chloride 4 were synthesized according to the literature [ 35 ]. 2a–2c were new compounds and their synthesis and characterization are described in electronic supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 Photochromic materials have attacked enormous attention for their potential applications in the areas of anti-fake, photoswitchable molecular devices, bio-labeling and optical memory storage systems. [19][20][21][22][23][24][25][26][27][28][29] Many photochromic systems with excellent photochromic properties have been designed and synthesized such as spiropyran, [30][31][32][33][34][35] azo-containing compounds, [36][37][38][39] and dithienylethene derivatives. [40][41][42][43][44][45][46] Beside promoted the photochromic properties, combining gated properties to photochromic molecules which could easily switch the photochromism was also an important issue.…”
Section: Introductionmentioning
confidence: 99%